Impact of Valve Culture in the Prognosis of Active Left-sided Infective Endocarditis. (11th August 2018) - García-Granja, Pablo Elpidio; López, Javier; Vilacosta, Isidre; Sarriá, Cristina; Ladrón, Raquel; Olmos, Carmen; Sáez, Carmen; Maroto, Luis; Di Stefano, Salvatore; Gómez, Itziar; San Román, J Alberto; ,
Abstract: Background: The culture of removed cardiac tissues during cardiac surgery of left-sided infective endocarditis (LSIE) helps to guide antibiotic treatment. Nevertheless, the prognostic information of a positive valve culture has never been explored. Methods: Among 1078 cases of LSIE consecutively diagnosed in 3 tertiary centers, we selected patients with positive blood cultures who underwent surgery during the active period of infection and in whom surgical biological tissues were cultured (n = 429). According to microbiological results, we constructed 2 groups: negative valve culture (n=218) and concordant positive valve culture (CPVC) (n=118). We compared their main features and performed a multivariable analysis of in-hospital mortality. Results: Patients with CPVC presented more nosocomial origin (32% vs 20%, P = .014), more septic shock (21% vs 11%, P = .007), and higher Risk-E score (29% vs 21%, P = .023). Their in-hospital mortality was higher (35% vs 19%, P = .001), despite an earlier surgery (3 vs 11 days from antibiotic initiation, P < .001). Staphylococcus species (61% vs 42%, P = .001) and Enterococcus species (20% vs 9%, P = .002) were more frequent in the CPVC group, whereas Streptococcus species were less frequent (14% vs 42%, P < .001). Independent predictors for in-hospital mortality were renal failure (odds ratio [OR], 2.6 [95% confidence interval CI, 1.5–4.4]), prosthesis (OR, 1.9 [95% CI, 1.1–3.5]), Staphylococcus aureus (OR, 1.8 [95% CI, 1.02–3.3]), and CPVC (OR, 2.3 [95% CI, 1.4–3.9]). Conclusions: Valve culture in patients with active LSIE is an independent predictor of in-hospital mortality. Abstract : Valve culture is an independent predictor of hospital mortality in active left-sided infective endocarditis. Patients in whom the same microorganism is isolated from blood and valve cultures had nearly 2-fold in-hospital mortality compared to those with negative valve culture.